Predictor Model of the Supply Chain Effectiveness based on Critical Sucess Factors in a Commerce Retail Industry - Da Gama, Scott; Hernández, Andrés; Escobedo, Maria Teresa; Noriega, Salvador (2022)
The business environments of the globalized economy present increasing complexity under highly variable conditions of volatility, risk, and uncertainty that exert intense pressures on retailers; some of them develop programs for the improvement of the supply chain. This paper is about determining the factors of the supply chain and the development of a structural equation model. The first section presents the background, the description of the problem and a literature search of the Supply Chain factors and their classification. The Methodology section explains the development of a questionnaire as a measuring instrument based on the identified factors. The validation of the questionnaire was with the Cronbach alpha index, and then it applied to a sample of retailers in central Mexico. Using the Partial Least Squares Structural Equation Modelling Approach, the development of a structural model identified the key driver factors related to the improvement of the Supply Chain. In results report the most important factors: 1) supplier’s quality of the goods, 2) internal factors, 3) after-sale service, and 4) road infrastructure and 5) commercial environment, for commerce retail industry in México.